Multiparty democracy : elections and legislative politics - Schofield, Norman (Cambridge University, 2013)
"This book adapts a formal model of elections and legislative politics to study party politics in Israel, Italy, the Netherlands, Britain, and the United States. The approach uses the idea of valence - that is, the party leader's non-policy electoral popularity - and employs survey data to model these elections. The analysis explains why small parties in Israel and Italy keep to the electoral periphery. In the Netherlands, Britain, and the United States, the electoral model is extended to include the behavior of activists. In the case of Britain, it is shown that there will be contests between activists for the two main parties over who controls policy. Regarding the recent 2005 election, it is argued that the losses of the Labour Party were due to Blair's falling valence. For the United States, the model gives an account of the rotation of the locations of the two major parties over the last century."